The Role of Kupang Class 1 Immigration Office in Handling Illegal Imigrants in East Nusa Tenggara - Yessi Sarlota Dodo; Gerald Aldytia Bunga (Fakultas Hukum Universitas Islam Al-Azhar Mataram, 2022)
The presence of foreigners both as Illegal Immigrants or Refugees and Asylum Seekers in Indonesia has increased each year. This causes the function of immigration control and enforcement to enforce immigration law becomes very important. The Kupang Class I Immigration Office is one of the immigration technical implementing units that implements policies and technical standardization in the field of immigration in the East Nusa Tenggara. The number of immigration actions carried out by the Kupang Class I Immigration Office tends to decrease from 2010 to 2015. However, the number of actions taken is still quite high. In carrying out its duties and functions, the Kupang Class I Immigration Office encountered problems in terms of the quantity of human resources. This causes not optimal handling of illegal immigrants. This study aims to determine the role of Class I Immigration Kupang in handling illegal immigrants and forms of coordination between agencies in the province of East Nusa Tenggara. This research method is empirical legal research. The data used in this study consisted of secondary data and primary data. The results showed that in handling illegal immigrants, the Kupang Class I Immigration Office carried out four roles, namely the role of discovery, the role of shelter, the role of security and the role of immigration control. This role is not carried out independently but involves other parties such as the Police, Indonesian Army, Regional Government and so on. The form of coordination carried out by the Kupang Class I Immigration Office with other agencies involved in handling illegal immigrants is the formation of the PORA Team and the implementation of coordination meetings. It is recommended that the Immigration Office need to increase socialization to related agencies regarding Presidential Regulation Number 125 of 2016 on Handling Refugees from Overseas, making community houses under the coordination of the PORA Team.